PENGEMBANGAN KEBAB SORGHUM BUMBU RENDANG (KAGUM) SEBAGAI PRODUK PANGAN LOKAL - Badraningsih Lastariwati, Satri Sidiq Pringgodani (Prosiding Pendidikan Teknik Boga Busana, 2020)
Indonesia is a tropical country that makes Indonesia as one of the countries that has biodiversity in the agricultural sector, but unprioritizes consumption and use of local products, making farmers less inculcating local food products such as sorghum (sorghum bicolor L. Moench). This research offers to find recipes for sorghum rendang kebab products, acceptance in the community and also nutritional tests for sorghum rendang kebabs. The type of research used is R & D (Research and Development) with a 4D development model (Define, Design, Develop, Disseminate). The place and time of research are Food Laboratory The Department of Food and Apparel Engineering Education, Faculty of Engineering, Yogyakarta State University is conducted from February to April 2019. In research applications using 3 percent of the appropriate product development, 20%, 40% and 60% that receive experts and the community about product development with a percentage of 40%. Agree from the examiner Agree that the value of the results received with the p test value is not much different. Receipt from the examiner cannot produce a value of 3.66 which means the product can be accepted in all aspects. Keywords : Local foods,Sorghum,Kebab,Rendang